Healing of erosions in rheumatoid arthritis remains elusive: results with 24 months of the anabolic agent teriparatide. (2nd January 2021) - Duryea, J; Gravallese, EM; Wortman, JR; Xu, C; Lu, B; Kay, J; Solomon, DH
Abstract : Objective: Erosion healing in rheumatoid arthritis (RA) is difficult to demonstrate. This extension study aimed to determine whether 2 years of teriparatide (TPTD) produces erosion healing. Method: Subjects in a previous 12 month randomized controlled trial of TPTD in RA were invited to receive 12 additional months of open-label TPTD. Eleven of the 24 original subjects were enrolled in the extension study, six of whom received TPTD in the final 12 months only. Subjects receiving 24 months of TPTD were assessed for reduction in erosion volume from baseline using computed tomography. We also compared erosion volumes between 12 and 24 months of TPTD. Large erosions in subjects receiving TPTD for 24 months were examined for volume change. Results: In the six patients who received 24 months of TPTD, there was no significant change in erosion volume at the metacarpophalangeal (MCP) and proximal interphalangeal (PIP) joints compared with baseline. The six subjects who received 24 months of TPTD had similar changes in erosion volume to the five who received 12 months of TPTD, in MCP (p = 0.17) and PIP (p = 0.63) joints. Assessment of large erosions in those receiving TPTD for 24 months showed no evidence of erosion healing. Conclusion: While this extension study was too small to be conclusive, we observed no evidence of reduction in erosion volume with the addition of TPTD for 24 months in subjects with RA in whom disease activity was controlled on a tumour necrosis factor inhibitor. This is consistent with our negative findings at 12 months.